2014
DOI: 10.1016/j.yrtph.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline toxicology: Overview of regulatory and product stewardship programs

Abstract: Significant efforts have been made to characterize the toxicological properties of gasoline. There have been both mandatory and voluntary toxicology testing programs to generate hazard characterization data for gasoline, the refinery process streams used to blend gasoline, and individual chemical constituents found in gasoline. The Clean Air Act (CAA) (Clean Air Act, 2012: § 7401, et seq.) is the primary tool for the U.S. Environmental Protection Agency (EPA) to regulate gasoline and this supplement presents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…IJOMEH 2017;30(1) 8 Wooden et al [70], who found that workers exposed to fuel experienced upper-airway inflammation, as evidenced by significant increases in MPO, IL-8, and nasal fluid vanadium levels. In one study [60], a 6-week daily exposure of animals to gasoline inhalation caused extensive histological changes to the epithelial cell lining of the bronchioles, including dilatation of the smooth endoplasmic reticulum, loss of secretory granules in the Clara cells, loss of ciliated cells, prominent nuclear alterations, necrotic type II pneumocytes, degeneration of the mitochondria, as well as some neoplastic changes.…”
Section: Respiratory Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…IJOMEH 2017;30(1) 8 Wooden et al [70], who found that workers exposed to fuel experienced upper-airway inflammation, as evidenced by significant increases in MPO, IL-8, and nasal fluid vanadium levels. In one study [60], a 6-week daily exposure of animals to gasoline inhalation caused extensive histological changes to the epithelial cell lining of the bronchioles, including dilatation of the smooth endoplasmic reticulum, loss of secretory granules in the Clara cells, loss of ciliated cells, prominent nuclear alterations, necrotic type II pneumocytes, degeneration of the mitochondria, as well as some neoplastic changes.…”
Section: Respiratory Toxicitymentioning
confidence: 99%
“…Since each of the BTEX compounds has an inherent toxic potential, workers at gasoline stations are the population at greatest risk of being simultaneously exposed to the synergistic and/or additive adverse effects of the gasoline constituents. Although the health and environmental hazards of gasoline had been previously documented through epidemiological and experimental studies over the past several decades [8], most of the study designs were outdated and thus were not conducted with contemporary fuels [9]. enquiry into patients' occupational history while trying to establish causality.…”
Section: Introductionmentioning
confidence: 99%
“…eir boiling points range from 35 to 200°C. 1,[4][5][6] Distillation is commonly used for separation of mixtures of volatile compounds due to di erences in their boiling points. It is used on an industrial scale for fractionation of petroleum (in re neries) as well as in the laboratory-scale sample preparation (e.g., before chemical analysis of complex samples).…”
Section: Introductionmentioning
confidence: 99%
“…Sulphur in gasoline is a direct contributor of SO X emissions. Nowadays, environmental concerns have resulted in legislation which places limits on the sulphur content of gasoline . Accordingly, a number of solutions have been suggested to reduce sulphur in gasoline, such as hydrotreating, adsorption, and extraction .…”
Section: Introductionmentioning
confidence: 99%